PENGARUH INTELLECTUAL CAPITAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Latukau, Nurlina Alifka; Syahdan, Rinto; Meliana, Meliana (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
The purpose of this study is to analyze the effect of intellectual capital and profitability on company value with financial distress as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The research method used is quantitative with the type of data secondary data. Data collection techniques use purposive sampling techniques. The model used in this study is panel data regression analysis using Eviews 12 as an analysis tool. The results of hypothesis testing in this study show that: (1) intellectual capital has no effect on company value, This indicates that intellectual capital has not been used as a decision-making tool, (2) profitability has a positive effect on company value, This shows that if the higher the profitability, the higher the value of the company, (3) intellectual capital does not affect the value of the company through Financial distress This shows that the disclosure of intellectual capital cannot affect financial distress which ultimately has an impact on the value of the company, (4) profitability affects the value of the company through financial distress.